The relationship between fiber intake and fat composition and hormone profile in women with central obesity - Lintang Mega Pertiwi; Ibnu Gunawan (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Central obesity is characterized by increased visceral and subcutaneous fat and is associated with metabolic and hormonal disturbances in women. This study aimed to analyze the relationship between dietary fiber intake and visceral fat, subcutaneous fat, and sex hormone–binding globulin (SHBG) levels in women with central obesity. A cross-sectional study was conducted in the Kediri Raya region in August 2025. The sample consisted of 70 women aged 19–45 years with a waist circumference greater than 80 cm, selected through purposive and quota sampling methods. A Semi-Quantitative Food Frequency Questionnaire was used to assess fiber intake. Visceral and subcutaneous fat were measured using Bioimpedance Analysis, and SHBG levels were obtained from blood samples. Statistical analyses included Pearson’s correlation, Fisher’s exact test, and multivariate linear regression adjusted for energy and macronutrient intakes. The results showed that fiber intake was significantly associated only with age (p= 0.026), but not with BMI, visceral fat, subcutaneous fat, or SHBG (p > 0.05). Multivariate analysis indicated that the carbohydrate–fiber interaction was negatively associated with BMI (p= 0.038) and visceral fat (p= 0.011). Conversely, fat–fiber interactions were positively associated with BMI (p= 0.008), visceral fat (p= 0.006), and subcutaneous fat (p= 0.035). No significant association was found between fiber intake and SHBG levels (p > 0.05). In conclusion, fiber intake in interaction with macronutrients influenced BMI and body fat composition but did not affect SHBG levels, highlighting the role of nutrient interactions in shaping visceral and subcutaneous fat tissue.